Susceptibility of some Rice Varieties to the Lesser Grain Borer, Rhyzopertha dominica Fab. (Coleoptera: Bostrichidae) in Benin - Chougourou, D.C.; Togola, A.; Nwilene, F.E.; Adeliossi, J.; Bachabi, F.; Oyetunji, O.E. (Science Alert, 2012)
The lesser grain borer, Rhyzopertha dominica, is a major primary insect of stored cereals worldwide. In Benin, it causes serious damages on paddy rice stored in rural zones. Nowadays, there is a big interest in developing alternative measures included the use of resistant varieties for controlling this key pest. For this purpose, a study was conducted at Africa Rice Center in 2008 to establish the resistance of 17 improved rice varieties included 13 NERICA, 2 Oryza sativa and 2 Oryza glaberrima to this pest. The varieties were artificially infested under laboratory conditions. The results showed that CG14, WAB56-50, WAB56-104 and NERICA4 had good resistance against the attack of Rhyzopertha dominica while NERICA10 and NERICA8 were highly susceptible. The most tolerant cultivars investigated from this study could be recommended for safe storage to reduce pest and economic losses in all endemic zones where R. dominica represents a major threat.